Recent progress in carbon-based composite materials for advanced sodium ion batteries: From storage mechanism to structural design to applications as flexible electrodes - Ao Song; Yunchao Li; Dingkun Yuan; Jie Wu; Hailin Gu; Guangxue Zhang; Angjian Wu; Jiangrong Xu (Green Energy & Environment)
Sodium ion batteries (SIBs) are one of the most prospective energy storage devices recently. Carbon materials have been commonly used as anode materials for SIBs because of their wide sources and low price. However, pure carbon materials still have the disadvantage of low theoretical capacity. New design and preparation strategies for carbon-based composites can overcome the problems. Based on the analysis of Na+ storage mechanism of carbon-based composite materials, the factors influencing the performance of SIBs are discussed. Adjustment methods for improving the electrochemical performance of electrodes are evaluated in detail, including carbon skeleton design and composite material selection. Some advanced composite materials, i.e., carbon-conversion composite and carbon-MXene composite, are also being explored. New advances in flexible electrodes based on carbon-based composite on flexible SIBs is investigated. The existing issues and future issues of carbon-based composite materials are discussed.